How is the concept analysis ability of high school students in Ilir Barat 1 Palembang? - Safira Permata Dewi; Siti Huzaifah; Djunaidah Zen (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
This study used the survey method to overview the concept analysis skills of high school students in Palembang City. This research was limited by the concept of the respiratory system and the circulatory system. The research sample (n=412) was a high school student from a school in Ilir Barat I District, Palembang City. The data was collected by using concept analysis questions, totalling 25 questions. The results showed that the concept analysis skills of high school students in Palembang City is “enough” (44,24%). The results of this study also showed that the analysis of the concept of high school students in Palembang City on the material of the respiratory system is better than the material of the circulatory system. The highest and lowest achievements per item can be seen in the respiratory system material (the highest achievement on item number 9 and the lowest achievement on item number 5). The results of this study indicated the importance of learning and assessment that train students' higher order thinking skills, so that concept analysis skills can also be increased.Abstrak Penelitian ini bertujuan untuk mendapatkan gambaran tentang kemampuan analisis konsep pada siswa SMA di Kecamatan Ilir Barat 1 Kota Palembang dengan menggunakan metode survei. Penelitian ini dibatasi oleh konsep sistem respirasi dan sistem peredaran darah. Sampel penelitian (n=412) merupakan siswa SMA yang berasal dari sekolah di Kecamatan Ilir Barat I Kota Palembang. Data dijaring dengan menggunakan soal analisis konsep yang berjumlah 25 soal. Hasil penelitian menunjukkan bahwa kemampuan analisis konsep siswa SMA di Kecamatan Ilir Barat 1 Kota Palembang terkategori cukup (44,24%). Hasil penelitian ini juga menunjukkan bahwa analisis konsep siswa SMA di Kota Palembang pada materi sistem respirasi lebih baik jika dibandingkan dengan materi sistem peredaran darah. Capaian tertinggi dan terendah per item soal terlihat pada materi sistem respirasi (capaian tertinggi soal nomor 9 dan capaian terendah pada soal nomor 5). Hasil penelitian ini menunjukkan bahwa pentingnya pembelajaran dan penilaian yang melatihkan kemampuan berpikir tingkat tinggi siswa, sehingga kemampuan analisis konsep pun dapat meningkat.